Integrasi Pertanian, Pariwisata, dan Digital untuk Ketahanan Sosial-Ekonomi di Desa Lombongo Kecamatan Suwawa Tengah Kabupaten Bone Bolango - Polamolo, Cristian; Hamin, Dewi Indrayani; Asnawi, Melan Angriani; Mohamad, Fajar Muslim (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2025)
This community service program in Lombongo Village aimed to optimize local potential by integrating agriculture, tourism, and digital technology to strengthen socio-economic resilience. The participatory implementation combined needs mapping, integrated outreach, hands-on training (bed gardening, composting, product downstreaming), basic tourism facility revitalization (installation of site maps and minor repairs), and digital literacy strengthening through social media accounts and a village website. Outcomes showed previously unused homegardens converted into productive bed systems, the launch of value‑added local products (Tortila Chips, Banana Meltzz, Candlenut Lemongrass), installation of visitor maps, and the establishment of a village website for information and promotion. Simple evaluation (pre/post tests and practice observation) indicated improvements in knowledge and partial adoption of sustainable farming practices and digital marketing by micro-entrepreneurs. In conclusion, the integrated interventions enhanced local capacities and created new economic opportunities, while continued mentoring, stronger downstreaming processes, and maintenance of tourism infrastructure are required to ensure lasting impact.